2015
DOI: 10.1371/journal.pone.0125791
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Glioblastoma Patients' Plasma Revealed the Presence of MicroRNAs with a Prognostic Impact on Survival and Those of Viral Origin

Abstract: BackgroundGlioblastoma multiforme (GBM) is among the most aggressive cancers with a poor prognosis in spite of a plethora of established diagnostic and prognostic biomarkers and treatment modalities. Therefore, the current goal is the detection of novel biomarkers, possibly detectable in the blood of GBM patients that may enable an early diagnosis and are potential therapeutic targets, leading to more efficient interventions.Experimental ProceduresMicroRNA profiling of 734 human and human-associated viral miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…Similarly, in the present study, we found EBV DNA in three out of 45 tissues, but not in the corresponding sera, possibly due to the very low amounts of EBV. In general, low levels of viral RNA in serum would indicate chronic infection, and in line with this, we found numerous viral miRNAs in the sera of 16 patients with GBM (39). Presumably in tissues, miRNAs allow for viral persistence and appear to inhibit cellmediated immunity, apoptosis, and the cell cycle, favouring the latency of infection.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, in the present study, we found EBV DNA in three out of 45 tissues, but not in the corresponding sera, possibly due to the very low amounts of EBV. In general, low levels of viral RNA in serum would indicate chronic infection, and in line with this, we found numerous viral miRNAs in the sera of 16 patients with GBM (39). Presumably in tissues, miRNAs allow for viral persistence and appear to inhibit cellmediated immunity, apoptosis, and the cell cycle, favouring the latency of infection.…”
Section: Discussionsupporting
confidence: 81%
“…Viruses can also change the host miRNA expression patterns, and make the infected cells more prone to oncogenic transformation. Previously, we identified 11 viral miRNAs that were differentially expressed in the plasma of patients with GBM, compared to those of healthy volunteers (39). These viral miRNAs induced signalling were mostly related to impaired immune responses in the progression of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…5F). Downregulation of the miR181 family is associated with glioma progression 31 , whereas the miR548 family is associated with prognosis and survival 32,33 . These results suggest that both families are potential therapeutic targets.…”
Section: Mirna-rna Interaction Analysis Indicate Mir548 Family In Cssmentioning
confidence: 99%
“…PPIA, also known as cyclophilin A, has roles across a range of biological processes, with essential functions in protein folding and chaperone activity [73]. PPIA overexpression is reported in various cancer types, its expression is influenced by chemotherapy [74,75] and PPIA has been reported to be a target gene of dysregulated miRNA species that are present in the plasma of GBM patients [76]. C3 is a member of the human complement system with key functions in innate immunity.…”
Section: Links To Previous Gbm-ev Studiesmentioning
confidence: 99%